A Study of the Influence of Intellectual Property on China–U.S. Trade Relations. (April 2020) - Li, Wei; Chen, Yichao
Recent investigations into China–U.S. trade relations have revealed that intellectual property plays an increasingly important role. A vector auto-regression model (VAR model) was established in this study to depict the relation among intellectual property protection, intellectual property trade barriers, and China–U.S. trade. Furthermore, Granger causality was utilized to formulate how intellectual property affects China–U.S. trade relations. As demonstrated by the relevant results, on one hand, intellectual property protection influences China–U.S. trade relations through the China–U.S. trade structure. On the other hand, China–U.S. trade relations may act on the intellectual property trade barrier for the same reason.